Bridging a 30 mm defect in the canine ulnar nerve using vessel‐containing conduits with implantation of bone marrow stromal cells. Issue 4 (14th March 2015) - Kaizawa, Yukitoshi; Kakinoki, Ryosuke; Ikeguchi, Ryosuke; Ohta, Souichi; Noguchi, Takashi; Oda, Hiroki; Matsuda, Shuichi
Abstract : Previously, we showed that undifferentiated bone marrow stromal cell (uBMSC) implantation and vessel insertion into a nerve conduit facilitated peripheral nerve regeneration in a rodent model. In this study, we investigated the efficacy of the uBMSC‐laden vessel‐containing conduit in repair of segmental nerve defects, using a canine model. Eight beagle dogs were used in this study. Thirty‐millimeter ulnar nerve defects were repaired with the conduits (right forelimbs, n = 8) or autografts (left forelimbs, n = 7). In the conduit group, the ulnar artery was inserted into the l‐lactide/ε‐caprolactone tube, which was filled with autologous uBMSCs obtained from the ilium. In the autograft group, the reversed nerve segments were sutured in situ. At 8 weeks, one dog with only nerve repair with the conduit was sacrificed and the regenerated nerve in the conduit underwent immunohistochemistry for investigation of the differentiation capability of the implanted uBMSCs. In the remaining seven dogs, the repaired nerves underwent electrophysiological examination at 12 and 24 weeks and morphometric measurements at 24 weeks. The wet weight of hypothenar muscles was measured at 24 weeks. At 8 weeks, almost 35% of the implanted uBMSCs expressed glial markers. At 12 weeks, amplitude (0.4 ± 0.4mV) and conduction velocity (18.9 ± 14.3m/s) were significantly lower in the conduit group than in the autograft group (3.2 ± 2.5 mV, 34.9 ± 12.1 m/s, P < 0.05). Although the nerve regeneration in the conduit group was inferior when compared with the autograft group at 24 weeks, there were no significant differences between both groups, regarding amplitude (10.9 ± 7.3 vs. 25.3 ± 20.1 mV; P = 0.11), conduction velocity (23.5 ± 8.7 vs 31.6 ± 20.0m/s; P = 0.35), myelinated axon number (7032 ± 4188 vs 7165 ± 1814; P = 0.94), diameter (1.73 ± 0.31 vs 2.09 ± 0.39μm; P = 0.09), or muscle weight (1.02 ± 0.40 vs 1.19 ± 0.26g; P = 0.36). In conclusion, this study showed that vessel‐containing tubes with uBMSC implantation may be an option for treatment of peripheral nerve injuries. However, further investigations are needed. © 2015 Wiley Periodicals, Inc. Microsurgery 36:316–324, 2016.